UIN SYAHADA Students' Perceptions About Internet Banking Service Security In Sharia Banking Transactions - Siregar, Sulaiman Efendi; Alfian, Ian; Ariani, Ade (Journal of Islamic Financial Technology, 2022)
The theories used in this research are the theories put forward by Bimo Walgito which discusses the notion of perception, various perceptions, factors that influence perception, the characteristics of perception, the process of perception, understanding of security, types of security systems. network, security indicators, basic components of a security system, understanding of internet banking, benefits of internet banking, advantages of internet banking, and security of internet banking transactions. This research uses descriptive qualitative method. The subjects of this study were students of the Islamic Economics and Business Faculty of UIN SYAHADA Padangsidimpuan class of 2017 and 2018 as many as 25 informantsThe results of this study regarding the perceptions of UIN SYAHADA Padangsidimpuan students about the security of internet banking services in Islamic banking transactions, the researchers conclude that the perceptions of UIN SYAHADA Padangsidimpuan students about internet banking services are very good where internet banking services are one of the banking services that allow customers to make transactions via the internet network. Because this service will really help students in making transactions such as checking balances, transferring money, paying tuition fees, buying credit vouchers and buying electricity tokens. Keywords: Perception, Security, Internet Banking Service